Ammonium quantification in human plasma by proton nuclear magnetic resonance for staging of liver fibrosis in alcohol‐related liver disease and nonalcoholic fatty liver disease. (9th May 2022) - Azagra, Marc; Pose, Elisa; De Chiara, Francesco; Perez, Martina; Avitabile, Emma; Servitja, Joan‐Marc; Brugnara, Laura; Ramon‐Azcón, Javier; Marco‐Rius, Irene
Abstract : Liver fibrosis staging is a key element driving the prognosis of patients with chronic liver disease. Currently, biopsy is the only technique capable of diagnosing liver fibrosis in patients with alcohol‐related liver disease (ArLD) and nonalcoholic fatty liver disease (NAFLD) unequivocally. Noninvasive (e.g. plasma‐based) biomarker assays are attractive tools to diagnose and stage disease, yet must prove that they are reliable and sensitive to be used clinically. Here, we demonstrate proton nuclear magnetic resonance as a method to rapidly quantify the endogenous concentration of ammonium ions from human plasma extracts and show their ability to report upon early and advanced stages of ArLD and NAFLD. We show that, irrespective of the disease etiology, ammonium concentration is a more robust and informative marker of fibrosis stage than current clinically assessed blood hepatic biomarkers. Subject to validation in larger cohorts, the study indicates that the method can provide accurate and rapid staging of ArLD and NAFLD without the need for an invasive biopsy. Abstract : Blood plasma treatment followed by 1 H‐NMR quantification of ammonium ion concentration was developed as a protocol to stage liver fibrosis. As an example application, the method is used to study differences in blood ammonium level between stages of alcoholic and nonalcoholic liver diseases.